2016
DOI: 10.1007/s00592-015-0825-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with the risk of development or progression of albuminuria among Japanese patients with type 2 diabetes: a prospective cohort study [Diabetes Distress and Care Registry at Tenri (DDCRT 10)]

Abstract: Low and high serum uric levels, independent of possible confounders, were associated with a subsequent risk of progression, not development, in albuminuria in type 2 diabetes patients. Therefore, serum uric acid levels may be useful for predicting the future risk of progression of microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 44 publications
1
43
1
1
Order By: Relevance
“…Similarly, we also found a statistically significant relationship between SUA concentration and the severity of albuminuria classified into three grades. Two prospective cohort studies reported an association between SUA and the development or progression of DN in patients with type 1 DM and type 2 DM, respectively [14,15]. In addition, the level of SUA was independently associated with the progression of albuminuria to macroalbuminuria early in the course of type 1 DM [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we also found a statistically significant relationship between SUA concentration and the severity of albuminuria classified into three grades. Two prospective cohort studies reported an association between SUA and the development or progression of DN in patients with type 1 DM and type 2 DM, respectively [14,15]. In addition, the level of SUA was independently associated with the progression of albuminuria to macroalbuminuria early in the course of type 1 DM [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of SUA was independently associated with the progression of albuminuria to macroalbuminuria early in the course of type 1 DM [14]. A prospective study from Japan demonstrated a significant association between higher baseline SUA level and the subsequent risk of DN progression in patients with type 2 DM [15]. …”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, MUO is characterized by higher albumin and CysC levels as compared to MHO. In addition, CysC, albumin, and UA were found to be sensitive in the identification of mild reductions in kidney function and could potentially identify young individuals at high risk for the future development of cardiometabolic diseases [49, 50]. These facts highlight that the association among UA levels and cardiometabolic disorders might be a relevant area of research, recognizing the implications of the discovery of potential new indicators and therapeutic targets in individuals with a metabolically unhealthy phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid (SUA) has been shown to be associated with reduced levels of 1.25(OH) 2 D via the inhibition of 1-α hydroxylase activity [9,10] as well as with microalbuminuria (MAU) [11] . This seems notable, since MAU is considered to be a biomarker for diagnosing diabetic kidney disease, and is a predictive factor for the progression to end-stage renal disease (ESRD) and increased cardiovascular risk among diabetic patients [12,13] .…”
Section: Introductionmentioning
confidence: 99%